Halo naevi and café au lait macule regression in a renal transplant patient on immunosuppression. (1st September 2014) - Lolatgis, Helena; Varigos, George; Braue, Anna; Scardamaglia, Laura; Boyapati, Ann; Winship, Ingrid
Abstract: A case of halo naevi and café au lait macule regression in a renal transplant patient receiving long‐term immunosuppressive therapy is described. We propose the direct transfer of an auto‐reactive antibody, CD8 T‐cells or tumour necrosis factor α from the transplant donor to the recipient as a possible cause. We have also considered insufficient immunosuppressive therapy as a possible mechanism.